A COMPARATIVE STUDY ON THE EFFECT OF THINK PAIR SHARE (TPS) AND THINK TALK WRITE (TTW) TECHNIQUES UPON STUDENTS' WRITING COMPETENCY OF EIGHTH GRADE IN SMP NEGERI 3 SAWAN IN ACADEMIC YEAR 2013/2014 - ., Ni Kadek Nia Novita Wiliani; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui perbedaan efektifitas teknik Think Pair Share dan Think Talk Write terhadap kemampuan menulis siswa. Penelitian ini menggunakan Randomized Post test Only Two Non-Control Group Design. Subjek penelitian terdiri dari 2 kelompok yang masing-masing terdiri dari 28 orang siswa. Kelas VIII A3 sebagai eksperimental kelompok X menggunakan teknik Think Pair Share dan kelas VIII A4 sebagai eksperimental kelompok Y menggunakan teknik Think Talk Write. Data dianalisis secara deskriptif dan inferensial. Dari hasil analisis deskriptif, rata-rata nilai untuk eksperimental kelompok X yaitu 76.53 lebih besar dibandingkan dengan eksperimental kelompok Y yaitu 72.28. Dari hasil analisis menggunakan statistik inferensial, telah ditemukan bahwa nilai observasi (tob) adalah 2.142. Nilai ini lebih tinggi dari nilai kritis (tcv) yaitu 2.0049 (É‘ = .05 dan df = 54) yang artinya bahwa hipotesis nol ditolak dan perbedaan diantara kedua kelompok adalah signifikan. Dari hasil tersebut, jelas bahwa ada perbedaan signifikan terhadap kemampuan menulis siswa yang diajar menggunakan teknik Think Pair Share dan Think Talk Write.Kata Kunci : Think Pair Share, Think Talk Write, Kemampuan Menulis This study aimed to investigate whether there is a significant difference between the studentsâ€™ writing competency of eighth grade in SMP Negeri 3 Sawan taught by using Think Pair Share and those who were taught using Think Talk Write technique. This study used â€œThe Randomized Post test Only Two Non-Control Group Designâ€ as the research design. The sample consisted of two groups, each group consisted of 28 students. VIII A3 class was assigned as experimental group X treated by using Think Pair Share technique and VIII A4 class was assigned as experimental group Y treated by using Think Talk Write technique. The data obtained were analyzed both descriptively and inferentially. The descriptive analysis showed that the mean score of experimental group X (76.53) was higher than the mean score of experimental group Y (72.28). The inferential analysis also showed that tobs (2.142) was higher than the tcv (2.0049) at the significant level .05 and the degree of freedom (df) was 54 which meant null hypothesis was rejected and the difference of the two groups were significant. From those result, it was clearly found that there was a significant difference on studentsâ€™ writing competency taught by using Think Pair Share technique and those taught using Think Talk Write technique. keyword : Think Pair Share, Think Talk Write, Writing Competency